Effect of bleaching agents and whitening dentifrices on the surface roughness of human teeth enamel - DENİZ, ŞULE TUĞBA; Ozkan, Pelin; Kansu, Gulay; Ozak, ŞULE TUĞBA; Kurtulmus-Yilmaz, Sevcan; Kansu, Pelin (My University, 2013)
Objective. The aim of this in vitro study was to evaluate the surface roughness of human enamel bleached with 10% carbamide peroxide or 10% hydrogen peroxide bleaching agents at different times and also subjected to different superficial cleaning treatments. Materials and methods. One hundred and forty flat enamel samples were divided into 14 groups, Group 1-Group 14 (G1-G14). G1-G7 were treated with 10% carbamide peroxide and different dentifrices, G8-G14 were treated with 10% hydrogen peroxide and different dentifrices (G1 and G8: not brushed as control groups; G2 and G9: brushed with Ipana (R) toothpaste; G3 and G10: brushed with Clinomyn (R) toothpaste; G4 and G11: brushed with Moos Dent (R) toothpaste; G5 and G12: brushed with Signal (R) toothpaste; G6 and G13: brushed with Colgate (R) toothpaste; G7 and G14: brushed without dentifrice). A profilometer was used to measure average roughness values of the initial surface roughness and at each 7-day-interval. The bleaching was performed for 6 h a day and the surface cleaning treatment was performed 3-times a day, 2 min each time, for 4 weeks. The samples were stored in distilled water during the test period. Results. Statistical analysis revealed significant differences in surface roughness values over time for all groups except G1 and G8 (not brushed). The results of the surface roughness of all groups were nearly the same. Conclusions. The bleaching with 10% hydrogen peroxide and 10% carbamide peroxide did not alter the enamel surface roughness, but when the bleaching treatment was performed combined with abrasive dentifrices, a significant increase in roughness values was observed.